Structural breaks and financial volatility: Lessons from BRIC countries - Lucía Morales; Esmeralda Gassie (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
Despite the fact that there is a substantial literature on the analysis of volatility spillovers between stock returns and domestic exchange rates, surprisingly, little empirical research has examined volatility spillovers between oil prices and emerging economies, where a clear gap of research have been found regarding to the BRIC financial markets and the effects of the 2007-2009 World economy crisis. This lack of research might appear as surprising given that energy markets are of particular interest as they are considered a fundamental reference for economic recovery and growth. Therefore, this work aims to address this gap on the literature by looking at the BRIC financial markets and their co-movements with regard to some energy markets (oil, natural gas and electricity) and also to the international pressures that may arise from fluctuations originated in the US stock markets. This research major findings show compelling evidence highlighting the weak integration levels that exist among the Chinese financial markets, energy markets and the US stock market. On the other hand, the Brazilian, Indian and Russian markets are found to be more sensitive to international shocks arisen from US markets and also to energy markets instability, especially with regard to oil market uncertainty.
Keywords: F; G; 330; BRIC; Energy Markets; GARCH; T-GARCH modeling; Volatility